Using CRISPRa and CRISPRi Technologies to Study the Biological Functions of ITGB5, TIMP1, and TMEM176B in Prostate Cancer Cells - Yang, Yi; Feng, Qingxing; Hu, Kun; Cheng, Feng (Frontiers in Molecular Biosciences, 2021)
Although ITGB5, TIMP1, and TMEM176B are abnormally expressed in several cancers, their molecular biological mechanisms in prostate cancer cells are still to be investigated. In this study, we used CRISPR interference (CRISPRi) and CRISPR activation (CRISPRa) technologies to regulate the transcription of ITGB5, TIMP1 and TMEM176B in prostate cancer cells. We found that inhibition of ITGB5 or activation of TIMP1 and TMEM176B suppress prostate cancer. The three genes synergistically affect the proliferation, invasion and migration capabilities of cancer cells.